Variant Allele Frequencies of Matched Primary and Locally Recurrent Breast Tumors - de Marchi, Tommaso (Lund University, 2023)
Variant allele frequencies (derived from TPES package using whole genome sequencing data) for samples with matching normal tissue. Allele frequencies for matched primary and recurrent tumors are reported as percentage.

This dataset was used for Supplementary Figure 7 in the following manuscript:

"Proteogenomics decodes the evolution of human ipsilateral breast cancer". De Marchi T, Pyl PT, Sjöström M, Reinsbach SE, DiLorenzo S, Nystedt B, Tran L, Pekar G, Wärnberg F, Fredriksson I, Malmström P, Fernö M, Malmström L, Malmström J, Nimèus E. accepted for publication
Keywords: Genomics and transcriptomics; Proteomics and metabolomics; Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik